Auxin‐mediated lamina growth in tomato leaves is restricted by two parallel mechanisms. (8th July 2016) - Ben‐Gera, Hadas; Dafna, Asaf; Alvarez, John Paul; Bar, Maya; Mauerer, Mareike; Ori, Naomi
Summary: In the development of tomato compound leaves, local auxin maxima points, separated by the expression of the Aux/IAA protein SlIAA9/ENTIRE (E), direct the formation of discrete leaflets along the leaf margin. The local auxin maxima promote leaflet initiation, while E acts between leaflets to inhibit auxin response and lamina growth, enabling leaflet separation. Here, we show that a group of auxin response factors (ARFs), which are targeted by miR160, antagonizes auxin response and lamina growth in conjunction with E. In wild‐type leaf primordia, the miR160‐targeted ARFs SlARF10A and SlARF17 are expressed in leaflets, and SlmiR160 is expressed in provascular tissues. Leaf overexpression of the miR160‐targeted ARFs SlARF10A, SlARF10B or SlARF17, led to reduced lamina and increased leaf complexity, and suppressed auxin response in young leaves. In agreement, leaf overexpression of miR160 resulted in simplified leaves due to ectopic lamina growth between leaflets, reminiscent of e leaves. Genetic interactions suggest that E and miR160‐targeted ARFs act partially redundantly but are both required for local inhibition of lamina growth between initiating leaflets. These results show that different types of auxin signal antagonists act cooperatively to ensure leaflet separation in tomato leaf margins. Significance Statement: Patterning in compound leaves involves auxin‐mediated lamina growth. We show that local restriction of lamina growth between leaflets, mediated by miR160‐targeted ARFs and the Aux/IAA protein ENTIRE, is required for the formation of distinct leaflets in tomato compound leaves.